Frequency of Tuberculosis and Malignancy in Transudative-pleural effusions: A rare but real finding - Abdul Rasheed Qureshi , Muhammad Irfan , Huma Bilal , Muhammad Sajid , Zeeshan Ashraf, Abdul Rasheed Qureshi , Muhammad Irfan , Huma Bilal , Muhammad Sajid , Zeeshan Ashraf (Journal of Rawalpindi Medical College, 2020)
Objectives: To determine the frequency of tuberculosis and malignancy in transudative pleural effusions. Material and Method: The study was conducted in Pulmonology-OPD, Gulab Devi Teaching Hospital Lahore from Oct. 2017 to Feb. 2019. One hundred and twenty-eight consecutive patients with transudative pleural effusions and 14-69 years age, willing for invasive investigations & ADA estimation were included, while those not willing for further investigations, participation in the study, and exudative effusions were excluded. The clinical features, pleural fluid analysis findings, ADA(Adenosine deaminase) estimation results, hematology, echocardiography, bronchoscopy, Lymph node biopsy, CT-thorax, ultrasound chest & abdomen results were recorded on a preformed proforma. Findings were summarized, tabulated, and analyzed statistically using SPSS-16 software. Results: Out of 1370 cases of pleural effusion, 128 cases (9.34%) with pleural transudate were isolated. In all patients, pleural fluid protein/serum protein level was < 0.5. The age ranged 14-69 years with a mean of 39 years + 11.3. Fifty-two cases (40.62%) had right-sided, 38 cases (29.68%) left-sided while 38 cases (29.68%) had bilateral pleural effusions. Seventy-six aspirates (59.37%) were yellow, 20 (15.62%) reddish, 18 (14.06%) straw-colored and 14 fluids (10.93%) were watery in color. Out of 128 transudative effusions, malignant etiology was found in 23 cases (17.96%), tubercular in 17 cases (13.28%) and 19 cases (14.84%) of Para-pneumonic origin were detected. Conclusion: Tuberculosis and malignancy can be the possible etiology of transudative effusion.